Transformasi UMKM Berdaya Saing Dan Berkelanjutan - Ratna Darasih; Maria Ariesta Utha; Dita Oki Berliyanti; Ayu Wulandari; Prameswari Dinda Lisanti (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
The objective of this Community Service (PkM) activity is to assist PKK (Family Welfare Empowerment) members in understanding competitive advantage strategies. This enables them to identify specific business actions for future management and the necessary mitigation measures to succeed in a competitive environment. This initiative addresses the fact that the businesses managed by PKK members in Ginanjar Village, Ciambar District, are generally small-scale start-ups. These MSME (Micro, Small, and Medium Enterprise) operators face various challenges—such as issues regarding capital, production techniques, labor, and marketing—alongside a limited understanding of competitive advantage strategies. The activity took place in Ginanjar Village, Ciambar District, Sukabumi Regency, on Thursday, January 15, 2026, with 29 members of PKK participating as beneficiaries. Results from the training and mentoring sessions indicate a 75% to 90% increase in the beneficiaries' knowledge regarding MSME concepts, the importance of product differentiation and low-cost strategies, and effective customer service—including handling complaints. Through this PkM program, it is hoped that MSME operators will recognize the significance and role of competitive advantage strategies, thereby transforming their ventures into resilient and reliable businesses capable of improving their families' economic well-being.